Rocking of a bell tower – Investigation by non-contact video measurement. (15th August 2019) - McCombie, Paul F.
Highlights: The forces generated by full-circle ringing of church bells are explained and illustrated. The relationship of these forces to the dynamic response of towers is explained. Observations of movement of a short tower are reported and discussed. The rocking response is shown to dominate for a short tower. This response is shown to be particularly susceptible to changes in ringing speed. Abstract: Church bells are rung in many historic towers, principally in United Kingdom, in a way which enables precise control of timing, and changes in the sequences of the bells – this is known as change ringing. The bells are heavy, many towers containing bells which weigh over a tonne. They are rung by swinging them on an axle through angles approaching 360°, applying substantial forces to the towers. These forces may cause structural damage, and movements of the tower that discomfort the ringers and can make ringing difficult or even dangerous. The movements of towers caused by ringing therefore concern both the ringers themselves, and the architects, engineers and authorities responsible for the historic buildings that house the bells. Movements are usually assumed to be caused by flexing of the bell towers. In this study video recording and imaging software has been used to show that a short tower moves by a combination of rocking on its foundations and bending of the masonry, associated with significantly different natural frequencies. It is shown that minor changes in the speed of the ringing can result in a forcing that works with or against these natural frequencies; the fundamental period of bending is much shorter than the fundamental period of the force from a bell, but the period of rocking is much longer. The significance of this longer period movement in short towers has not been previously recognised, as it has not been detected by the accelerometers normally used in investigations of tower movement. This investigation therefore advances understanding of bell tower movements, but also demonstrates the capability of the video recording and image processing used in the investigation.